Synergistic effects of sorafenib in combination with gemcitabine or pemetrexed in lung cancer cell lines with K-ras mutations - Wang, Shu; Su, Zeng-feng; Yuan, Yuan; Li, Jing (Contemporary Oncology/Współczesna Onkologia, 2016)
K-ras is currently accepted as the most frequently mutated oncogene in non-small cell lung cancer (NSCLC, including squamous carcinoma, adenocarcinoma, and large cell carcinoma). NSCLC patients with the K-ras mutation appear to be refractory to the majority of systemic therapies. In the present study, the in vitro antitumor effects and correlated molecular mechanisms of sorafenib combined with gemcitabine or pemetrexed were explored in the K-ras mutation-positive NSCLC A549 cell line. Sorafenib was seen to exhibit dose-dependent growth inhibition in the A549 cells, while sorafenib combined with pemetrexed demonstrated a greater synergism compared with sorafenib combined with gemcitabine. Sorafenib arrested the cell cycle at the G1 phase, while gemcitabine and pemetrexed caused arrest at the S phase. The molecular mechanism of this synergism was due to the downstream signalling pathways, which were efficiently suppressed by sorafenib, therefore increasing the incidence of the entry of the chemotherapeutic drugs into the apoptotic pathways. Moreover, sorafenib and pemetrexed demonstrated stronger synergism, demonstrating that inhibiting the Ras/Raf/Mek/Erk and Ras/PI3K/Akt pathways concurrently may achieve improved antitumor effects.